Blastemal predominant WT1 negative Wilms tumour of the young adult: a unique case report and review of the literature - Jozef Škarda; Jozef Škarda; Michal Grepl; Michal Grepl; Valeria Skopelidou; Valeria Skopelidou; Vladimír Židlík; Vladimír Židlík; Vladimír Židlík; Pavel Hurník; Pavel Hurník; Pavel Hurník; et al. (Frontiers in Medicine)
Wilms tumour is a common juvenile cancer of the kidney, and its occurrence in adolescence or adulthood is extremely rare, accounting for around 1% of all adult kidney malignancies. Histopathologically, three tissue patterns can be identified, including blastemal, epithelial, and stromal components, while the overall microscopic appearance of an adult-type tumour does not differ from that of its juvenile counterpart. The blastemal predominant Wilms tumours are the most aggressive and have the worst prognosis. The samples must be histopathologically verified before the definitive diagnosis can be made, and immunohistochemistry examination is critical. Wilms tumours are often positive for keratin, vimentin, desmin, actin, and WT1, which distinguishes this type of tumour from other malignancies. WT1 positivity is indicative of the blastemal component of the tumorous tissue and may be completely absent in the mature epithelial and stromal parts. Only three WT1 negative adult-type Wilms tumours have been reported in the literature to this date. However, none of the patients had a blastemal predominant tumour. That is why we would like to present a highly interesting and diagnostically challenging case of a young man who was diagnosed with a tumorous lesion of the left kidney parenchyma. Genetic analysis did not reveal any known fusion genes associated with round cell sarcomas, ruling out this differential diagnosis. This article also includes a literature review on published articles on WT1 negative Wilms tumour in adults and other concerns related to this topic. The main goal of this publication was to emphasise that, while it is a rare entity in general, similar problematic cases can occur in practise, and thus it is important to be aware of this type of tumour when making a differential diagnosis in cases with similar clinical and histopathological features.